2011
DOI: 10.1111/j.1600-0447.2011.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of correlates of physical activity in patients with schizophrenia

Abstract: All correlates should be confirmed in prospective studies, and interventions to improve the modifiable variables should be developed and evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
189
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(217 citation statements)
references
References 60 publications
12
189
3
2
Order By: Relevance
“…2015;37 (4) Schizophrenia and physical exercise Rev Bras Psiquiatr. 2015;37 (4) sets of 10 to 15 maximum repetitions of resistance exercises for six different muscle groups per week. 35 These sessions lasted 1 hour and took place twice a week for 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2015;37 (4) Schizophrenia and physical exercise Rev Bras Psiquiatr. 2015;37 (4) sets of 10 to 15 maximum repetitions of resistance exercises for six different muscle groups per week. 35 These sessions lasted 1 hour and took place twice a week for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…5 These authors also advocated the use of concurrent training to optimize the regulation of glucose metabolism, increase lean body mass, and improve body composition, as well as prevent the bone loss that is prevalent among patients with schizophrenia. 4,38 A recent pilot study assigned patients with schizophrenia to a maximum strength-training program for their legs to investigate whether this type of training would improve the mechanical efficiency of walking. The intervention protocol consisted of four sets of four repetitions of 85 to 90% 1RM leg-press exercises three times a week over 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on physical activity correlates in patients with schizophrenia and schizoaffective disorder showed that longer illness duration and more severe negative symptoms are associated with a sedentary lifestyle and lack of physical activity (Vancampfort et al, 2012e;Vancampfort et al, 2013a).…”
Section: Factors Associated With the Astrand-rhyming Test Performancementioning
confidence: 99%
“…In the general population there is evidence that physical activity and exercise are broadly as effective as pharmacological interventions in preventing cardiovascular disease and mortality (Naci and Ioannidis, 2013). However, people with psychosis experience a range of barriers to engage in physical activity such as negative symptoms, pain and the side effects of medication (Soundy et al, 2014a;Vancampfort et al, 2012a;Vancampfort et al, 2011).…”
Section: Introductionmentioning
confidence: 99%